Addie model course design for the creative industry department - Tjahyanto, Mario Christian Noer (Journal of Applied Studies in Language, 2022)
As one of the general requirement subjects in universities in Indonesia, English is taught in all of the departments in the university. If the English class is not managed carefully, students may become unmotivated in taking the class since it may have little or no relation to the actual subject that they are taking at the university. Therefore, it is necessary to design an English course that can engage the student's interests and suit students’ needs. This research aimed to develop a course that is most suitable for the students in Creative Industry Department. In doing so, this research used a research and development procedure called the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to develop the course and the materials. The process began with the needs analysis of the lecturers and the head of the Creative Industry Department, followed by the design of the course materials. Then, the course was implemented for the whole semester, and the cycle of the process ended with distributing questionnaires to the students who participated in the course. The result showed that the course could meet the target set by the head of the department, which was to increase students’ confidence in using English.